1998
DOI: 10.1136/hrt.80.6.627
|View full text |Cite
|
Sign up to set email alerts
|

Junctional ectopic tachycardia evolving into complete heart block

Abstract: Transition from congenital junctional ectopic tachycardia to complete AV block was observed in an 8 month old girl, over a 36 hour period, during initial hospital admission. Two years later she had evidence of a rapidly increasing left ventricular end diastolic diameter, associated with lowest heart rates during sleep of < 30 beats/min. A transvenous permanent pacemaker was therefore implanted. This finding supports the idea that a pathological process in the area of the AV junction, initially presenting as ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 3 publications
(3 reference statements)
1
11
0
Order By: Relevance
“…Atrial pacing may restore AV synchrony in a subset of patients with JET at the price of a slightly higher heart rate. However, as observed in this and other reports, 6 impaired AV conduction is frequently revealed after institution of atrial pacing. An attempt on AV resynchronization by atrial pacing is then impossible and results in first‐ or higher degree AV block.…”
Section: Discussionsupporting
confidence: 73%
“…Atrial pacing may restore AV synchrony in a subset of patients with JET at the price of a slightly higher heart rate. However, as observed in this and other reports, 6 impaired AV conduction is frequently revealed after institution of atrial pacing. An attempt on AV resynchronization by atrial pacing is then impossible and results in first‐ or higher degree AV block.…”
Section: Discussionsupporting
confidence: 73%
“…JET is considered a rare arrhythmia presenting at the ECG with narrow ventricular complexes, AV dissociation, and QRS morphology resembling that of sinus beats 1–18 . Invasive electrophysiology has demonstrated that each ventricular electrogram is preceded by a “leading” His bundle deflection with an HV interval that has to be compatible with ante grade conduction (> 35 ms) 1–3,14,15 …”
Section: Discussionmentioning
confidence: 99%
“…Some authors underlined the importance of His bundle fibers extensive disruption or focal degeneration and split, 3,19 while others described structural abnormalities of the whole AV junction 20 . A recent report of a congenital JET evolving into complete AV block supported the idea of a progressive disease involving the AV junction that had manifested in different ways 11 . Whatever the pathological background, JET may be more commonly encountered in pediatric patients, occurring as a postoperative complications of surgical interventions that involve interventricular septum manipulation or cause damage to the AV conduction system 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mother has subsequently developed symptomatic palpitations and shows electrocardiographic features consistent with typical atrioventricular nodal re-entrant tachycardia (AVNRT) on symptom-rhythm correlation observed on loop recorder. Thus, the conduction defects in this family were of varying severity and the relationship to congenital JET in the three children is important as it is well recognized that congenital JET may progress to heart block [1,2]. At this stage the conduction abnormalities are minor in the twins who presented with the JET and have not progressed.…”
mentioning
confidence: 89%